Factor that impact the adoption of reuse practices among Malaysians - Hashim, Ahmad Hariza; Zainal Badari, Shamsul Azahari (Malaysian Consumer and Family Economics Association, 2024)
Sustainable consumption is important globally, but it is challenging to practice. Many people care about the environment and support sustainability, yet this often does not change what they buy. Consumerism, which focuses on personal enjoyment and status, harms the environment and creates waste. Reusing items essential for sustainable consumption has not been studied much, even though it can help products last longer. This study examines Malaysian consumers' awareness of environmental issues, sustainability knowledge, and willingness to reuse items. The goal is to find out what encourages people to reuse. The study used a detailed survey to collect information from different parts of Malaysia, focusing on Peninsular Malaysia, Sabah, and Sarawak. In Peninsular Malaysia, four regions were studied: Northern (Kedah), Central (Selangor), Eastern (Terengganu), and Southern (Johor). 1,023 participants participated, including 481 from Peninsular Malaysia, 253 from Sabah, and 289 from Sarawak. Participants were randomly chosen from various government organisations to ensure a mix. Results show that most people are aware of environmental issues and want a suitable living environment. While they know some sustainability terms, they could better understand more complex ideas. The analysis shows a strong link between understanding sustainability, being aware of environmental issues, and wanting to reuse and reuse items. The willingness to reuse is the most significant factor affecting reuse habits. By improving understanding of sustainability, raising awareness of environmental issues, and promoting a reuse culture, waste can be reduced and lessen its environmental impact.